(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Now a day in metropolitan cities air and sound pollution becomes serious issues, because of high decibels and toxic gases present within the environment which directly effect on human health and thus needs a special attention. Therefore, it’s now become necessary to regulate the pollution (air and noise) to ensure healthy livelihood and better future. In this paper, an efficient implementation for Internet of Things is employed for monitoring atmospheric conditions of environment like air pollution and noise pollution. And also we monitor The Temperature and Humidity. Using MQ7 sensor for sensing Carbon Monoxide (CO) and MQ135 gas Sensor for detecting wide range of gases, including NH3, NOx, alcohol, benzene, smoke and CO2.constantly transmit this data. Also, system keeps measuring sound level using MIC sensor and reports it. DHT11 sensor consists of a capacitive Humidity sensing element and Thermistor for sensing Temperature. Soil moisture is the amount of water in the soil. Soil moisture monitoring system that helps the govt authorities to understand the data about dry soil areas within the agricultural lands within a village, town or maybe a state so that the required precautionary steps will be taken to create such lands fertile.